A Unique Reverse Adaptation Mechanism Assists Bordetella pertussis in Resistance to Both Scarcity and Toxicity of Manganese - Čapek, Jan; Procházková, Ilona; Matoušek, Tomáš; Hot, David; Večerek, Branislav (mBio, 2021)
The ability of bacterial pathogens to acquire essential micronutrients is critical for their survival in the host environment. Manganese plays a complex role in the virulence of a variety of pathogens due to its function as an antioxidant and enzymatic cofactor. Therefore, host cells deprive pathogens of manganese to prevent or attenuate infection. Here, we show that evolution of the human-restricted pathogen Bordetella pertussis has selected for an inhibitory duplication within a manganese exporter of the calcium:cation antiporter superfamily. Intriguingly, upon exposure to toxic levels of manganese, the nonfunctional exporter becomes operative in resister cells due to a unique reverse adaptation mechanism. However, compared with wild-type (wt) cells, the resisters carrying a functional copy of the exporter displayed strongly reduced intracellular levels of manganese and impaired growth under oxidative stress. Apparently, inactivation of the manganese exporter and the resulting accumulation of manganese in the cytosol benefited the pathogen by improving its survival under stress conditions. The inhibitory duplication within the exporter gene is highly conserved among B. pertussis strains, absent from all other Bordetella species and from a vast majority of organisms across all kingdoms of life. Therefore, we conclude that inactivation of the exporter gene represents an exceptional example of a flexible genome decay strategy employed by a human pathogen to adapt to its exclusive host. IMPORTANCE Bordetella pertussis, a respiratory pathogen restricted to humans, continuously adapts its genome to its exclusive host. We show that speciation of this reemerging pathogen was accompanied by loss of function of the manganese exporter. Intriguingly, the functionality of the exporter can be restored in the presence of toxic levels of manganese by a unique genetic modification. However, compared with the wt strain, the strain carrying the functional exporter failed to resist the oxidative stress in vitro. Thus, our data demonstrate that inactivation of the exporter resulting in manganese accumulation assists B. pertussis in adaptation to oxidative stress. We conclude that this sophisticated process of reverse adaptation enables B. pertussis to adjust to rapidly changing environments by facilitating its resistance to both manganese toxicity and manganese scarcity.
Keywords: pertuse; regulace genové exprese u bakterií; bakteriální proteiny; Manganese; Oxidative Stress; Bacterial Proteins; Gene Expression Regulation, Bacterial; Bordetella pertussis; virulence; Virulence; Virulence Factors; lidé; oxidační stres; Whooping Cough; faktory virulence; mangan; Humans